RFID antenna for smart shelf - Li, Peng. (2009)
The project addresses the problem by presenting an analytical model for a 3-dimensional single folded loop antenna with detection coverage in space. Based on the antenna theory, the inductance and impedance of the loop antenna is investigated. Design issues including antenna topology, read range, tag orientations, proximity of metal and other antennas are addressed to determine proper antenna for optimal performance. The proposed design is verified by field distribution measurement and implemented as a RFID reader antenna for smart shelf application. The built-in sensor is designed to detect book movement based on SWR variance. Without extra power supply, the sensor uses the power from the reader. The functionality eliminates the need of manual monitoring all the time and improves the application performance.